PARALLEL BUREAUCRACIES AND POLITICAL LEADERSHIP: DUPLICATION AND EXPROPRIATION OF FUNCTIONS IN THE ARGENTINE PRESIDENTIAL CENTER (1916-2016) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
Beyond bureaucracies used to manage routine relationships with their environment, Executive Branch leaders can use the center of government as a political resource to face nonroutine situations and centralize policy formulation. This resource is the creation of what I call “director agencies”, i. e.: agencies that duplicate or expropriate functions and roles until then assigned to other agencies, departments, and personnel of the Executive. Through a statistical regression analysis for the period 1916-2016 in Argentina, it is concluded here that economic and political uncertainty, neo-corporatism, and regime type, affect the use and creation of “director agencies” in the center of government.
Keywords: Bureaucracy, Leadership, Executive Branch, Institutional Presidency